Modelling the relationships between training, anxiety, and fatigue in elite athletes - Millet, G. P.; Groslambert, A.; Barbier, B.; Roullion, J. D.; Candau, R. B. (International Journal of Sports Medicine, 2005)
This study investigated the effects of 40-week training on anxiety and perceived fatigue in four elite triathletes. Anxiety and perceived fatigue were self-reported by the subjects twice a week by the way of a specific questionnaire and were linked by a mathematical model to the training loads calculated from the exercise heart rate. A significant relationship (r = 0.32; p < 0.001) between the training loads and anxiety was identified using a two-component model: a first, negative (i.e., anxiety decreased) short-term (t1 = 23 days) function and a second, positive long-term (t2 = 59 days) function. The relationship between the training loads and perceived fatigue was significant (r = 0.30; p < 0.001), with one negative function (t1 = 4 days). This mathematical model can potentially describe the relationships between training loads and anxiety or perceived fatigue and may improve both the adjustment of the duration of tapering and the early detection of staleness.